Decadal to Multidecadal Variability of the Atlantic MOC: Mechanisms and Predictability - Latif, Mojib; Böning, Claus W.; Willebrand, Jürgen; Biastoch, Arne; Alvarez, F.; Keenlyside, Noel (AGU (American Geophysical Union), 2007)
The dynamics and predictability of the decadal to multidecadal Atlantic meridional overturning circulation (MOC) variability are described from observations and models. The investigation focuses on two modes that involve the MOC: One mode exhibits a quasi-decadal period, while the other is multidecadal. The two modes have completely different underlying dynamics, which is reflected in their rather different spatial characteristics. While the quasi-decadal mode represents a damped mode of the coupled ocean-atmosphere system, the multidecadal mode can be basically understood as the MOC response to the multidecadal forcing by the North Atlantic Oscillation (NAO). "Perfect model" predictability studies indicate a rather high predictability potential of the MOC variability on decadal timescales. Variations of the MOC are associated with variations in the meridional heat transport that drive sea surface temperature (SST) anomalies. SST anomalies in the North Atlantic thus exhibit a similar decadal predictability potential as the MOC. The decadal predictability carries over to the atmosphere. The probability density function of European surface air temperature anomalies, for instance, changes significantly with the state of the MOC. A reconstruction of the MOC for the 20th century from observed SSTs shows considerable variability on decadal timescales, but no strong sustained long-term trend. Furthermore, an assessment of the observed hydrographical changes in the Nordic Seas, with the aid of ocean general circulation model experiments and the analysis of recent scenario integrations with global climate models, indicates that the expected anthropogenic weakening of the MOC may not exceed the level of the internal variability within the next decades.